Synthesis and Characterization of Anatase Titanium Dioxide Nanoparticles Using Egg White Solution via Sol-Gel Method - Samira Bagheri; Kamyar Shameli; Sharifah Bee Abd Hamid (Journal of Chemistry)
Anatase titanium dioxide nanoparticles (TNPs) are synthesized by a simple and cost-effective process with and without freshly water-soluble egg white proteins (albumin) via sol-gel method. The main advantage of using egg white proteins as a gelling agent is that it can provide long-term stability for nanoparticles by preventing particles agglomeration. The X-ray diffraction and FTIR results indicate that the synthesized nanoparticles have only the anatase structure without the presence of any other phase impurities. Additionally, the TNPs are characterized by a number of techniques such as thermogravimetric analysis (TGA), X-ray diffraction analysis (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and ultraviolet visible spectra (UV-vis). The sizes of titanium dioxide nanoparticles with and without using egg white solution are 12.55±3.42 nm and 21.45±4.21 nm, respectively. The results indicate that egg white solution is a reliable and cheap green gelling agent that can be used as a matrix in the sol-gel method to synthesis tiny size TNPs.